Delivery Technique for Fibular Strut Bone Grafting to Proximal Humerus Nonunion Fractures. Issue 4 (December 2021) - Kane, Steven M.; Tanaka, Scott; Smith, Matt
Abstract : Introduction: The prevalence of proximal humerus fractures will continue to increase as the population ages. Although the use of fibular strut grafts to treat these fractures is well established and has been used for many years, the authors present an alternative technique that aligns the graft within the intermedullary canal, and proximal segment, allowing for greater fragment and reduction control throughout the procedure. Materials and Methods: The technique involves intramedullary reaming and the usage of a #5 suture through the strut graft proximally that allows for easy placement of the graft across the fracture and into the humeral head after reduction. Results: The representative case described in this paper demonstrates a simplified technique for placement of a fibular allograft and fracture reduction with locking plate fixation for the treatment of proximal humerus nonunions. Discussion: The technique is an effective and simple method for the placement of a fibular strut allograft within the intramedullary canal of the distal and proximal segments of a proximal humeral fracture. The use of an endosteal fibular allograft strut addresses the need to re-establish the medial column of the humerus, provides local bone stock, and helps avoid varus angulation, and allows for improved fixation of the plate in poor quality bone.